Efektivitas Pembelajaran Mufradat dengan Menggunakan Media Puzzle Book pada Siswa Kelas VII MTs Darul Istiqamah Babang Luwu - Nurhikma Nurhikma; Naidin Syamsuddin; Mubassyirah Bakri (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims (1) to determine the ability of mastery of mufradat in seventh grade students of Madrasah Tsanawiyah Babang Luwu before and after applying puzzle book media. (2) to determine the effectiveness of puzzle book media in improving mastery of mufradat for seventh grade students of Madrasah Tsanawiyah Babang Luwu. The method used in this research is Classroom Action Research (PTK) with Kemmis and McTaggart model which consists of two cycles. Data were collected through observation, tests, and interviews. The results of this study are (1) classroom action research conducted by researchers can be concluded that the use of puzzle book media is effective to be applied to seventh grade students (Research Class) by looking at the increase in the results of students' mastery of mufradat which increased through puzzle book media. (2) The percentage increase in cycle I can be seen that out of 23 students, 10 students with a percentage of (43%) were complete, while 13 students with a percentage of (57%) were not complete. As for cycle II, it can be seen that out of 23 students, 19 students were complete with a percentage (83%), while those who were not complete were 4 students with a percentage (17%). From cycle I to cycle II there was an increase in learning outcomes by (40%). Thus in cycle II the learning outcomes were said to be complete.